If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(10k + 9) + -7(1 + -4k) = y Reorder the terms: 5(9 + 10k) + -7(1 + -4k) = y (9 * 5 + 10k * 5) + -7(1 + -4k) = y (45 + 50k) + -7(1 + -4k) = y 45 + 50k + (1 * -7 + -4k * -7) = y 45 + 50k + (-7 + 28k) = y Reorder the terms: 45 + -7 + 50k + 28k = y Combine like terms: 45 + -7 = 38 38 + 50k + 28k = y Combine like terms: 50k + 28k = 78k 38 + 78k = y Solving 38 + 78k = y Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-38' to each side of the equation. 38 + -38 + 78k = -38 + y Combine like terms: 38 + -38 = 0 0 + 78k = -38 + y 78k = -38 + y Divide each side by '78'. k = -0.4871794872 + 0.01282051282y Simplifying k = -0.4871794872 + 0.01282051282y
| 74x+7= | | (2x^2+2x+18)+(3x^2-4x+13)-(x^2+15x-2)=0 | | 6(x-3)=-3x-54 | | f(x)=9x^2+54x+71 | | (5g^3+2)-(6g+6)-(4g^3-3g)=0 | | (7b^4-4)-(7b^3-5)+(4b^4-3b^3)=0 | | secx+cosx=0 | | 2r^2-10r-48=0 | | 3(9n+5)+8(10n-9)=y | | 4(3x-1)+9(-5x+2)=y | | 9(6a-10)+2(-6a+8)=y | | 6(4k-5)-4k=y | | -9(2-10a)+8a=y | | 3(1+8m)=y | | 4(9+4x)=y | | f(x)=2x^2-36x+169 | | 6x+43=300 | | -6(8+x)-7=y | | 7(-6m-8)+9m=y | | 10(-2b+8)+2=y | | 10(1-6v)=y | | 10(1-6v)=y | | 7(x*6)+y=119 | | -6(b-2)=y | | 5x^3=8 | | x^4+x^3+x+4=0 | | -7(10p-7)=y | | -4p-2p=y | | 2a-10a=y | | 1-8n-9n=y | | x*7+45=80 | | 2x+y=74 |